A study on ChatGPT for Industry 4.0: Background, potentials, challenges, and eventualities - Mohd Javaid; Abid Haleem; Ravi Pratap Singh (Journal of Economy and Technology)
ChatGPT is an Artificial Intelligence (AI)-powered Natural Language Processing (NLP) tool that comprehends and produces text in response to given commands. It can be adopted for various requirements, like answering our inquiries, assisting us with content creation, translating languages, and more. The fourth industrial revolution, called ''Industry 4.0,'' denotes a new production age focused on automation, digitalisation, and real-time connectivity of production systems. ChatGPT can help Industry 4.0 in a variety of ways. ChatGPT and AI-driven process optimisation is poised to revolutionise Industry 4.0 by enhancing productivity, quality assurance, and efficiency. For developing this paper, various articles on ChatGPT/ AI for Industry 4.0 were identified through Scopus, ScienceDirect, Google Scholar and ResearchGate. Industry 4.0 progresses due to the incorporation of cutting-edge technology like AI, Machine Learning (ML), and NLP and Manufacturing operations are changing. The ChatGPT language model is becoming well-known for daily use because of its promising applications. In the framework of Industry 4.0, it promises to revolutionise processes to assist advancement in boosting business productivity and efficiency. This paper studies the major need for ChatGPT for Industry 4.0. Various associated features, traits and versatile competencies of ChatGPT for Industry 4.0 are identified and briefed. Finally, it identifies and discusses the significant applications of ChatGPT for Industry 4.0. ChatGPT is a very flexible and efficient method for creating human-machine interfaces and automatically generating text, which provides proper knowledge and guidance to the employee. Applications for ChatGPT include chatbots, virtual assistants, automated customer care, language translation, and content production. In future, it will become an effective tool for enhancing communication and automating processes in Industry 4.0.